Comparison of Transcranial Sonography and [18F]‐Fluorodopa PET Imaging in GBA1 Mutation Carriers - Eisenberg, Daniel P.; Lopez, Grisel; Gregory, Michael D.; Berman, Karen F.; Sidransky, Ellen (Movement disorders, 2022)
Background Mutations in GBA1 are a common genetic risk factor for parkinsonism; however, penetrance is incomplete, and biomarkers of future progression to parkinsonism are needed. Both nigral sonography and striatal [18F]‐FDOPA PET assay dopamine system health, but their utility and coherence in this context are unclear. Objective The aim of this study is to evaluate the utility and coherence of these modalities in GBA1‐associated parkinsonism. Methods A total of 34 patients with GBA1 mutations (7 with parkinsonism) underwent both transcranial studies for substantia nigra echogenicity and [18F]‐FDOPA PET to determine striatal tracer‐specific uptake (Ki). Results Larger nigral echogenic areas and reduced striatal Ki were exclusively observed in parkinsonian patients. Sonographic and PET measurements showed strong inverse correlations but only in individuals with clinical parkinsonism. Conclusions Close correspondence between nigral echogenicity and striatal presynaptic dopamine synthesis capacity observed only in GBA1 carriers with parkinsonism provides validation that these two modalities may conjointly capture aspects of the biology underlying clinical parkinsonism but raises questions about their utility as predictive tools in at‐risk subjects. © 2022 International Parkinson and Movement Disorder Society